Modified technique for the visualisation of C6/C7 in the lateral cervical spine radiography - Moey, Soo Foon; Hazri, Najwa Athirah; Che Mohamed, Norfariha (Mashhad University of Medical Sciences, 2019)
Introduction: In the Swimmer’s projection, occasionally the C6 and C7 can be visualized superimposed on the thick anatomy of the shoulders. This study aims to explore the technique to demonstrate C1 to C7 in the lateral spine and to improve the diagnostic value in that region. Materials and Methods: An experimental study was carried out by using a RANDO phantom to obtain the images of the lateral cervical spine. Twelve radiographs were taken using different kVps at different centering points. Two radiographers evaluated the image quality of the radiographs using the modified image quality criteria score sheet adapted from the Commission of European Communities on image quality. A DAP meter was utilized to estimate the entrance surface dose while CALDose_X 5.0 Monte Carlo was used to estimate the effective dose. Results: The findings indicated that a higher centering point at two inches above pinna of the ear can visualize the lower cervical spine; C6/C7 and the cervicothoracic junction (C7/T1). The Kruskal-Wallis test also indicated significant differences (p<0.05) in the image quality at different centering points. However, no significant differences were found (p>0.05) in the ESD between different centering points utilized. The effective dose of the modified technique was found to be lower compared to the Swimmer’s View. Conclusion: The modified lateral technique can be used to replace the Swimmer’s View as it can adequately demonstrate the lower cervical spine; C6/C7 and the cervicothoracic junction with a lower radiation dose while not harming the patient due to movement during positioning.